Las elocutiones de Servio y Arusiano - Magallón García, Ana Isabel (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
The well-known grammarian Servius, active at the end of the 4th and beginning of the 5th Century, included in his grammatical and exegetical explanations the concept of elocution as a “syntactic construction”. Its only two known antecedents are to be found in Carminius, an author active at the middle of the 4th century, whose work was quoted by Servius but lost to us, and o Arusianus, never mentioned by his almost contemporary Servius, although we can deduce from studying their respective works that the former had influenced the latter. By retrieving such missing link, this paper reconstructs a continuity in the use of the concept of elocutio from Arusianus to Servius revealed by those study-cases.